On the Ternion Cubical Diophantine Equation 5(\(m^2\) + \(n^2\)) -6(\(mn\)) + 8(\(m\)+ \(n\)) + 16 = 370\(p^3\) - P. Saranya; G. Janaki; K. Poorani (Explorations in Diophantine Equations, 2023)
The third order Cubic Diophantine equation 5(\(m^2\) + \(n^2\)) -6(\(mn\)) + 8(\(m\)+ \(n\)) + 16 = 370\(p^3\) is analyzed for infinitely enormous number of non-zero integer solutions. Also, some fascinating relations among the solutions are exhibited.